Enhanced sunlight photocatalytic activity and biosafety of marine-driven synthesized cerium oxide nanoparticles - Somayeh Safat (Nature Portfolio, 2021)
Abstract This contribution presents the biosynthesis, physiochemical properties, toxicity and photocatalytic activity of biogenic CeO2 NPs using, for the first time, marine oyster extract as an effective and rich source of bioreducing and capping/stabilizing agents in a one-pot recipe. CeO2 NPs formation was initially confirmed through the color change from light green to pale yellow and subsequently, their corresponding absorption peak was spectroscopically determined at 310 nm with an optical band-gap of 4.67 eV using the DR-UV technique. Further, XRD and Raman analyses indicated that nanoceria possessed face-centered cubic arrangements without any impurities, having an average crystallite size of 10 nm. TEM and SEM results revealed that biogenic CeO2 NPs was approximately spherical in shape with a median particle size of 15 ± 1 nm. The presence of various bioorganic substances on the surface of nanoparticles was deduced by FTIR and TGA results. It is found that marine-based nanoceria shows no cytotoxic effect on the normal cell, thus indicating their enhanced biocompatibility and biosafety to living organisms. Environmentally, due to energy band gap, visible light-activated CeO2 nanocatalyst revealed superior photocatalytic performance on degradation of methylene blue pollutant with removal rate of 99%. Owing to the simplicity, cost-effectiveness, and environmentally friendly nature, this novel marine biosynthetic route paves the way for prospective applications of nanoparticles in various areas.